The Exposition of University Youth to Television Advertising and its Reflection on the Development of their Cognitive Abilities A survey of students (College of Media / University of Baghdad) as ample - Majid, Mohammed Khadim (ALBAHITH ALALAMI, 2019)
This research is aimed at identifying the communicative habits and the impact of the content on the communicative process, especially the youth audience, which is one of the most important categories to which the advertisement is directed, as young people face life with passion and aspiration that make then responsive to all the influences used by the media in designing advertisements which use all the techniques and methocls to attract young people, such as relying on drama , artistic tricks, musical phrases and advertising slogans that respond to the desire of young people in entertainment. The research aims to identify the reflection of television advertising and its impact on the development of the cognitive abilities of university youth as well as identify the most prominent effects that have been reflected on them. The researcher used the descriptive method, which allows him to survey the performance of the communicative medium and the communication message together in accordance with the research requirements. The research uses the questionnaire as a field to explore their views on the subject of university youth exposure to television advertising and its reflection on the development of their cognitive abilities. The research has reached many conclusions, the most important of which is that television advertising has a positive impact on university youth in developing their cognitive abilities and a great role in teaching students how to convince and attract others, and the nature of television advertising requires a high mental level of thinking, understanding and enhancing information among students